FRI0108 ASSOCIATION BETWEEN CHANGES IN C-REACTIVE PROTEIN AT WEEK 12 AND PATIENT-REPORTED OUTCOMES AT WEEK 24 WITH SARILUMAB THERAPY ACROSS THREE PIVOTAL PHASE 3 STUDIES. (2nd June 2020) - Tesser, J.; Wright, G. C.; Strand, V.; Kaine, J.; Maslova, K.; St John, G.; Ford, K.; Praestgaard, A.; Choy, E.
Abstract : Background: Evaluation of early response to rheumatoid arthritis (RA) therapy at 12 weeks after initiation is recommended in treatment guidelines. C-reactive protein (CRP) response at 12 weeks on therapy may indicate favorable longer-term patient-reported outcomes (PROs). Objectives: To describe the association between CRP response at Week 12 and PROs at Week 24 with sarilumab therapy across three pivotal studies. Methods: The analysis included patients with RA who took part in MOBILITY (NCT01061736 ), TARGET (NCT01709578 ), or MONARCH (NCT02332590 ) and were treated with sarilumab 200 mg every 2 weeks (q2w) or adalimumab 40 mg q2w (MONARCH only). Patients who achieved a CRP response at Week 12 (defined as serum CRP ≤3 mg/L) were evaluated for PROs at Week 24. Response for PROs was defined as change from baseline visual analog scale score ≥10 for pain, sleep, and morning stiffness and an increase of ≥4 for FACIT-Fatigue score. Odds ratios (ORs) and 95% confidence intervals (CIs) were generated for the likelihood of achieving PRO responses at Week 24. Results: The proportions of patients achieving a CRP response at Week 12 were 78% (MOBILITY), 74% (TARGET), 80% (MONARCH, sarilumab), and 36% (MONARCH, adalimumab). Of these, 71.4% (MOBILITY; OR 3.78, 95% CI 2.31–6.18), 71.5% (TARGET; OR 2.86, 95% CI 1.44–5.65), 79.7% (MONARCH, sarilumab; OR 4.40, 95% CI 2.04–9.47), and 79.7% (MONARCH, adalimumab; OR 2.76, 95% CI 1.36–5.61) reported pain score responses at Week 24. Fatigue responses at Week 24 among Week 12 CRP responders were 66.6% (MOBILITY; OR 2.74, 95% CI 1.69–4.45), 59.9% (TARGET; OR 3.18, 95% CI 1.58–6.42), 73.0% (MONARCH, sarilumab; OR 4.78, 95% CI 2.21–10.33), and 64.1% (MONARCH, adalimumab; OR 1.64, 95% CI 0.88–3.06). Sleep was evaluated in MOBILITY only, and 58.2% of those achieving Week 12 CRP responses reported sleep score responses at Week 24 (OR 3.51, 95% CI 2.10–5.87). Morning stiffness responses (evaluated in TARGET and MONARCH only) at Week 24 among patients with Week 12 CRP responses were 71.5% (TARGET; OR 3.70, 95% CI 1.86–7.39), 81.1% (MONARCH, sarilumab; OR 5.36, 95% CI 2.47–11.63), and 75.0% (MONARCH, adalimumab; OR 2.42, 95% CI 1.24–4.72). Conclusion: Achievement of a CRP response at Week 12 in patients with RA treated with sarilumab 200 mg q2w or adalimumab 40 mg q2w was associated with improvements at Week 24 in PROs for pain, fatigue, sleep, and morning stiffness. Among patients with RA, CRP responses at 12 weeks on treatment predict favorable longer-term PRO improvements. Acknowledgments: Study funding was provided by Sanofi Genzyme (Cambridge, USA) and Regeneron Pharmaceuticals, Inc. (Tarrytown, USA). Medical writing support (Tracey Lonergan, Adelphi Communications Ltd, Macclesfield, UK) was provided by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. in accordance with Good Publication Practice (GPP3) guidelines. Disclosure of Interests: John Tesser Consultant of: Sanofi/Regeneron, Speakers bureau: Sanofi/Regeneron, Grace C. Wright Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Exagen, Eli Lilly, Myriad Autoimmune, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Sanofi Genzyme, UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Exagen, Eli Lilly, Myriad Autoimmune, Novartis, Regeneron Pharmaceuticals, Inc., Sanofi Genzyme, UCB, Vibeke Strand Consultant of: AbbVie, Amgen, Biogen, Celltrion, Consortium of Rheumatology Researchers of North America, Crescendo Bioscience, Eli Lilly, Genentech/Roche, GlaxoSmithKline, Hospira, Janssen, Merck, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Sanofi, UCB, Jeff Kaine Speakers bureau: Eli Lilly, Merck, Regeneron Pharmaceuticals, Inc., Sanofi, Karina Maslova Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, Gregory St John Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., Kerri Ford Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, Amy Praestgaard Employee of: Sanofi Genzyme, Ernest Choy Grant/research support from: Amgen, Bio-Cancer, Chugai Pharma, Ferring Pharmaceuticals, Novimmune, Pfizer, Roche, UCB, Consultant of: AbbVie, Amgen, AstraZeneca, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Chelsea Therapeutics, Chugai Pharma, Daiichi Sankyo, Eli Lilly, Ferring Pharmaceuticals, GlaxoSmithKline, Hospita, Ionis, Janssen, Jazz Pharmaceuticals, MedImmune, Merck Sharp & Dohme, Merrimack Pharmaceutical, Napp, Novartis, Novimmune, ObsEva, Pfizer, R-Pharm, Regeneron Pharmaceuticals, Inc., Roche, SynAct Pharma, Sanofi Genzyme, Tonix, UCB, Speakers bureau: Amgen, Boehringer Ingelheim, Bristol-Myers Squibb, Chugai Pharma, Eli Lilly, Hospira, Merck Sharp & Dohme, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Roche, Sanofi-Aventis, UCB